0 投票
422 浏览
分类:中学其它科目 | 用户: (13,780 分) 85 97 101
已关闭 用户:

If P = D(1 + yt), rearrange the formula so that the subject is D.

已关闭

2 个回答

+3 投票
用户: (46,890 分) 17 50 59
采纳于 用户:
 
已采纳

P=D(1+yt)

P ÷ (1+yt) = D(1+yt) ÷ (1+yt)

P ÷ (1+yt) = D(1+yt) ÷ (1+yt)

P/(1+yt)=D

D=P/(1+yt)

0 投票
用户: (18,820 分) 9 25 41

If change the (1+yt) to other side,it will be division p. So,

P = D(1+yt) 
P/(1+yt) = D
D = P/(1+yt) 

This plan is more easier.Hope its can help you.
 

“eWenda e问答”是一个专为马来西亚华裔生所建立的学业疑问问答平台。学生可以在这里免费发表提问并得到解答。
...